Immunological behavior of in vitro digested egg‐white lysozyme. Issue 3 (1st October 2013) - Jiménez‐Saiz, Rodrigo; Benedé, Sara; Miralles, Beatriz; López‐Expósito, Iván; Molina, Elena; López‐Fandiño, Rosina
<x xml:space="preserve">Abstract</x> Scope Besides its antimicrobial properties, lysozyme (LYS) is one of the major allergens from hen egg. This paper addresses the identification of the peptides produced upon in vitro gastrointestinal digestion of LYS, together with their IgE‐binding and biological activity as a contribution to the understanding of what makes it a relevant allergen. Methods and results Simulated in vitro gastrointestinal digestion together with IgE binding, basophil degranulation, and peripheral blood mononuclear cells stimulation experiments were carried out. Identification of the fragments released was performed by HPLC‐MS/MS and the immunoreactive products were analyzed by MALDI‐TOF/TOF. Results showed that in vitro gastric and gastroduodenal digests of LYS maintained IgE binding, basophil activation capacity, and preserved T‐cell immunogenicity. These biological activities could be attributed to either the persistence of intact LYS, due to incomplete gastric degradation and subsequent duodenal precipitation, the formation of fragment f(24–129) by chymotrypsin action on the soluble intact protein, or the release, upon combined gastric and pancreatic digestion, of immunoreactive peptides linked by disulphide bonds containing the epitopes f(57–83) and f(108–122). Conclusion The pH of gastric hydrolysis greatly determined the extent of subsequent duodenal digestion of LYS and the disclosure of relevant epitopes that could increase its allergenic potential.